Anticancer mechanism of 7-α-hydroxyfrullanolide on microtubules and computational prediction of its target binding in triple-negative breast cancer cells - Siriphorn Chimplee; Carl Smythe; Varomyalin Tipmanee; Suchada Sukrong; Kanyanatt Kanokwiroon (PeerJ, 2022)
Background Triple-negative breast cancer (TNBC) responds poorly to the available drugs; thus, the mortality rate associated with TNBC remains high. 7-α-Hydroxyfrullanolide (7HF) possesses anticancer properties and arrests cells in the G2/M-phase via modulation of several proteins involved in the G2/M-phase transition, as well as the mitotic checkpoint in MDA-MB-468 (TNBC) cells. Microtubules (MTs) dynamically regulate cell division in the G2/M phase and are related to cancer cell stress response. However, antimitotic drug cytotoxicity to multiple cancer resistance developed in response to drugs are obstacles faced to date. Here, the activity and mechanism via which 7HF controls MTs dynamics was investigated in MDA-MB-468 cells. Methods 7HF uptake by MDA-MB-468 cells was assessed using spectrophotometry. The drug-like properties of 7HF were predicted using the Swiss-absorption, distribution, metabolism, and excretion (ADME) webtool. Then, the effect of 7HF treatment (6, 12, and 24 µM) on the dynamic arrangement of MTs was assessed for 1, 12, and 24 h using indirect immunofluorescence. Polymerization of α- and β-tubulin was assessed using different 7HF concentrations in a cell-free system for 1 h. Cell proliferation assay with bromodeoxyuridine plus propidium iodide staining and flow cytometry was performed at different 7HF concentrations and time points. The mechanism of action was assessed by detecting the expression of proteins, including Bub3, cyclin B1, p-Cdk1 (Tyr15), Rb, p-Rb (Ser780), Chk1, p-Chk1 (Ser345), Chk2, p-Chk2 (Ser516), and p-H2AX (Ser139), using western blotting. Molecular docking was used to predict the molecular interactions between 7HF and tubulins in MTs. Results We observed that 7HF was able to enter the MDA-MB-468 cells. The ADME webtool analysis predicted that it possesses the high passive permeation and gastrointestinal absorption properties of drugs. Various concentrations of 7HF disrupted the dynamic arrangement of spindle MTs by causing radial spindle array shrinkage and expansion of fibrous spindle density and radial array lengths in a time-dependent manner. 7HF reduced polymerization of α-, β-tubulin in dose-dependent manner. 7HF also triggered DNA damage response by inducing G2/M and G1 phase arrests in a concentration and time-dependent manner, which occurred due to the upregulation of Bub3, Chk1, p-Chk1 (Ser345), p-Cdk1 (Tyr15), and cyclin B1. According to molecular docking analysis, 7HF preferred to bind to β-tubulin over α-tubulin. The lactone, ketone, and hydroxyl groups of 7HF supported the 7HF-tubulin interactions. Hydrogen bonding with a hydrocarbon ring and salt bridge attractive forces were responsible for the binding versatility of 7HF. Conclusions This is the first study to investigate the molecular mechanism, MTs interacting sites, and the internalization and drug-like properties of 7HF in TNBC cells. The findings will be useful for developing 7HF-based treatment for patients with TNBC.